Pengaruh Gaya Kepemimpinan Transformasional, Kompensasi Dan Budaya Organisasi Terhadap Produktivitas Kerja Karyawan Pada Koperasi Unit Desa Pakis Kabupaten Malang - Muhammad Munir; Abdul Kodir Djaelani; Muhammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis research was conducted at the Village Unit Cooperative Pakis Malang Regency. The is aim of this research was for test and reasearching influence of transformational leadership style, compensation and organizational culture on the work productivity of employees of the Desa Pakis Unit Cooperative in Malang Regency.The variables used are transformational leadership style, compensation and organizational culture as an independent variable, while employee productivity is the dependent variable. The sample used in this study was 37 employees of the Desa Pakis Village Cooperative Unit in Malang Regency. The study uses descriptive statistical analysis and inferential statistics. Data collection method by collecting primary data. The test use test instrument testing, classical assumption test, normalitys tests, multiple linear regression, hypothesis testing and coefficient of determination tests using multiple regression analysis using SPSS 24.0.The results research that the transformational leadership style variables and organizational culture did not influence significantly the work productivity of the Pakis Village Unit Cooperative employees of Malang Regency, while the compensation variable had a significant effect on the work productivity of the Pakis Village Unit Cooperative Employees of Malang Regency. Keywords: Transformational Leadership Style, Compensation, Organizational Culture and Employee Work Productivity